RETRACTED: Exploring morality and politeness in the context of robotic systems: A conceptual interpretation - Tikhanychev Oleg (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001